ความรู้เบื้องต้นเกี่ยวกับหุ่นยนต์เคลื่อนที่อัตโนมัติ - นัถฤทธิ์, พนัส (Naresuan University Engineering Journal, 2014)
บทความนี้มีจุดมุ่งหมายเพื่อนำเสนอพื้นฐานความรู้และเทคโนโลยีของหุ่นยนต์เคลื่อนที่ตั้งแต่อดีตจนถึงปัจจุบัน รวมไปถึงการศึกษาทฤษฎีและหลักการต่างๆ ที่เป็นองค์ประกอบสำคัญในการควบคุมหุ่นยนต์ให้สามารถเคลื่อนที่ได้เองโดยอัตโนมัติจากจุดเริ่มต้นไปสู่จุดหมายปลายทางโดยไม่มีการปะทะ เฉี่ยวชนหรือแม้แต่สัมผัสกับสิ่งกีดขวางใดๆ ที่เป็นอุปสรรคขัดขวางการเคลื่อนที่ของหุ่นยนต์ไม่ให้เข้าสู่จุดหมายปลายทางได้ Introduction to Autonomous Mobile Robot This paper addresses the essential knowledge related to mobile robot navigation. In the paper, the relevant information regarding research in mobile robotics area is presented including background and their history, control architecture, navigation, sensor system, and software. The robot architecture is the foundation of control in mobile robot while the navigation system enables the robot to safely navigate to its final destination. Sensors assist the mobile robot to determine its internal status and acquire information of external surrounding. All knowledge described above are finally integrated and programmed into the software to undertake a number of specifics tasks.